The Potential of Industrial Agglomeration to Promote Pharmaceutical Innovation: Analysis of China's "Medicine Valley" Construction Upsurge. Issue 6 (30th November 2022) - Fan, Jianting; Zhao, Fusen; Zhao, Yuhao
Abstract: This paper reports the innovation effect of pharmaceutical industry agglomeration from the perspective of patterns of agglomeration and innovation, by using registration application data for innovative and generic drugs as indicators of pharmaceutical innovation. First, the distribution of the pharmaceutical industry in China is characterized by high agglomeration and low innovation. Second, no significant influence is exerted by regional industrial and development zone agglomeration on the development of innovative drugs in different regions; the effect of the promotion of generic drugs is reflected mainly in the location entropy index. Third, the existence of a crowding effect weakens the effect of the promotion of agglomeration on pharmaceutical innovation and the adverse impact on innovative drugs is significantly greater than the effect on generic drugs. In further research, we explored the bias effect of agglomeration in development zones and the synergistic effects of different agglomeration models. It is difficult to improve the quality of independent innovation by spatial agglomeration. Government‐led development zones play a rather limited role in pharmaceutical innovation.